2018
DOI: 10.18203/2319-2003.ijbcp20184862
|View full text |Cite
|
Sign up to set email alerts
|

A surveillance study of cutaneous adverse drug reactions in a tertiary care teaching hospital in India

Abstract: Background: Skin is one of the most common targets of adverse drug reactions (ADRs) The practice of pharmacovigilance all over the world is 5% whereas in India, it is below 1%. Hence, the purpose of our study is to monitor and analyze the suspected cutaneous adverse drug reactions (ACDRs) reported at our tertiary care teaching hospital, to characterize the nature and predictability, severity and preventability of ACDRs and identify most common drugs causing cutaneous ACDRs so that they can be given cautiously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…More ADRs were reported from males (55.86%) in the study conducted by Badar et al which was similar to our study. 6 A higher percentage of ADRs occur in adult age group (31-45 years) in our study. Maximum numbers of ADRs were reported in the age group of 31-40 years by Badar et al 6 The department reporting maximum ADRs (63.01%) was from dermatology department in the study conducted by Lilute et al 7 In the present study also, maximum number of ADRs were reported from skin department.…”
Section: Discussionsupporting
confidence: 39%
See 2 more Smart Citations
“…More ADRs were reported from males (55.86%) in the study conducted by Badar et al which was similar to our study. 6 A higher percentage of ADRs occur in adult age group (31-45 years) in our study. Maximum numbers of ADRs were reported in the age group of 31-40 years by Badar et al 6 The department reporting maximum ADRs (63.01%) was from dermatology department in the study conducted by Lilute et al 7 In the present study also, maximum number of ADRs were reported from skin department.…”
Section: Discussionsupporting
confidence: 39%
“…6 A higher percentage of ADRs occur in adult age group (31-45 years) in our study. Maximum numbers of ADRs were reported in the age group of 31-40 years by Badar et al 6 The department reporting maximum ADRs (63.01%) was from dermatology department in the study conducted by Lilute et al 7 In the present study also, maximum number of ADRs were reported from skin department. The most common drug class causing the ADRs in our study is antimicrobials (38%).…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…16 In oner other study it was seen that CADRs was more common with amoxicillin-clavulanic acid (18.95%), ciprofloxacin (14.91%), amoxicillin (14.11%) and others which is in accordance with our study. 17 The most common group of drugs associated with fixed drug eruption were AMAs ofloxacin, sulfamethoxazole. This is in conformity with studies done in India reports of sulfonamide being emerging as the most common cause of Fixed drug eruptions (FDE).…”
Section: Discussionmentioning
confidence: 99%